The discovery and development of aclidinium bromide for the treatment of chronic obstructive pulmonary disease. (3rd June 2018) - Malerba, Mario; Radaeli, Alessandro; Santini, Giuseppe; Morjaria, Jaymin; Mores, Nadia; Mondino, Chiara; Macis, Giuseppe; Montuschi, Paolo
ABSTRACT: Introduction : Bronchodilators, including long-acting muscarinic receptor antagonists (LAMAs), are a mainstay of the pharmacological treatment of chronic obstructive pulmonary disease (COPD). LAMAs act as bronchodilators principally by antagonizing airway smooth muscle cells M3 muscarinic receptors. Aclidinium bromide is a twice-daily LAMA which was developed to improve on the efficacy and/or safety of previous LAMAs. Area covered : Herein, the authors present the pharmacotherapeutic role of aclidinium in COPD and point out unmet need in this research area. The following aspects are covered: a) the discovery and medicinal chemistry of aclidinium bromide; b) an overview of the market; c) its mechanism of action; d) its pharmacokinetic/pharmacodynamic profile derived from pre-clinical studies; e) the clinical studies which led to its licensing; f) the evidence from meta-analyses; g) the aclidinium/formoterol fixed dose combination for COPD and h) priorities in this area of research. Expert opinion : Aclidinium bromide has the pharmacological properties, safety and efficacy profile and inhaler characteristics which makes it a valuable therapeutic option for pharmacological management of patients with COPD. Due to its rapid biotransformation into inactive metabolites, aclidinium is potentially one of the safest LAMAs. Further head-to-head randomized clinical trials are required to define efficacy and safety of aclidinium when compared to once-daily LAMAs. The clinical relevance of airway anti-remodeling effects of aclidinium has to be defined.